PELAKSANAAN MUHADHARAH DI PONDOK PESANTREN AL-MIZAN LAMONGAN - Anggraeni, Ariskha; Haryanto, Budi (PAI RAFAH, 2024)
This article is motivated by the specialty of muhadharah activities carried out by Al-Mizan Lamongan IslamicBoarding School in improving Santri's da'wah competence. This study aims to provide more specific guidance and identify the potential of santri in more depth the ability of santriwati in public speaking. The method is disqualitative method. The methods disqualitative method Data collection techniques through observation were conducted from October to September 2023. The results ofthis study indicate that the implementation of muhadharah activities will have a positive impact on students, in order to form the character of self-confidence of students at the Ai-Mizan Lamongan Islamic Boarding School. From the muhadharah activities there have produced cadres of mubali ghawho are favored by the community